Membudayakan Pendidikan Nilai-Nilai Islami Dalam Membangun Karakter Siswa - Yudi Kuswandi (STAI Siliwangi Bandung, 2016)
The important role shown by formal educational institutions is very effective in cultivating Islamic values ​​for the formation of characters expected by the Indonesian nation. The activities of professional practitioners combine consistent constellation of values, goals, sanctions, knowledge and methods manifested in the form of certain moral ideas. Concrete operational form expressed in daily deeds with the level of system and target that has been determined, into its own value in growing the character istiqamah. Values ​​are a key element in the social structure that influences the basic orientation, belief system, as well as the actions of individuals and social institutions. Values ​​influence the guidelines or criteria for the appearance of a person's character behavior. Although in other studies the family character education may be more effective, but in this study the character culture values ​​in formal education institutions are more effective because psychologically the learners will be more obedient, afraid, and reluctant to the teacher than the parents or the general public. The main key is consistent in the application of rules, evaluation, reward and punishment in applying religious, moderate, intelligent, independent, and national character which serve as the benchmark for successful implementation of Islamic values ​​to shape the nation's character. The methods adopted in this study site may be grounded theory designs in the formation of Islamic values ​​in order to have a generation of characters that are rolled out by the government, amidst the moral, mental and character crises of learners and teenagers in general.Finally, if in this study many shortcomings or errors can be retested by the same methods and tools and generate new conclusions that may be the same or may be different. Suggestions and suggestions from various parties that are competent are expected to improve the writing and research.